Early use of methylene blue in vasoplegic syndrome: a 10-year propensity score matched cohort study - Kofler, Othmar; Simbeck, Maximilian; Tomasi, Roland; Hinske, Ludwig Christian Giuseppe; Klotz, Laura Valentina; Uhle, Florian; Born, Frank; Pichlmaier, Maximilian; Hagl, Christian Matthias; Weigand, Markus A.; Zwißler, Bernhard; Dossow, Vera von (Journal of Clinical Medicine, 2022)
Background: Vasoplegic syndrome is associated with increased morbidity and mortality in patients undergoing cardiac surgery. This retrospective, single-center study aimed to evaluate the effect of early use of methylene blue (MB) on hemodynamics after an intraoperative diagnosis of vasoplegic syndrome (VS). Methods: Over a 10-year period, all patients diagnosed with intraoperative VS (hypotension despite treatment with norepinephrine ≥0.3 μg/kg/min and vasopressin ≥1 IE/h) while undergoing heart surgery and cardiopulmonary bypass were identified, and their data were examined. The intervention group received MB (2 mg/kg intravenous) within 15 min after the diagnosis of vasoplegia, while the control group received standard therapy. The two groups were matched using propensity scores. Results: Of the 1022 patients identified with VS, 221 received MB intraoperatively, and among them, 60 patients received MB within 15 min after the diagnosis of VS. After early MB application, mean arterial pressure was significantly higher, and vasopressor support was significantly lower within the first hour (p = 0.015) after the diagnosis of vasoplegia, resulting in a lower cumulative amount of norepinephrine (p = 0.018) and vasopressin (p = 0.003). The intraoperative need of fresh frozen plasma in the intervention group was lower compared to the control group (p = 0.015). Additionally, the intervention group had higher creatinine values in the first three postoperative days (p = 0.036) without changes in dialysis incidence. The 90-day survival did not differ significantly (p = 0.270). Conclusion: Our results indicate the additive effects of MB use during VS compared to standard vasopressor therapy only. Early MB administration for VS may significantly improve the patients’ hemodynamics with minor side effects.